On the classification of the Lie algebras Lr,ts - L. A-M. Hanna (International Journal of Mathematics and Mathematical Sciences)
The Lie algebras Lr,ts introduced by the author (2003) are classified from an algebraic point of view. A matrix representation of least degree is given for each isomorphism class.